Kalman Filter parameter estimation for Vanadium Redox Flow Battery (V-RFB) equivalent circuit with parasitic inductance - Siti Fadhilah, Mohamed Ibrahim (2019)
Vanadium Redox Flow Battery (V-RFB) is a type of rechargeable flow battery that employs vanadium ions in different oxidation states. It undergoes oxidation and reduction reaction during discharge and charge process at anode and cathode. Presently, there are lack of publication studies on electrical circuit model for V-RFB. Electrochemical model is commonly use to represent battery due to its detailing in electrochemical process, however, the model is not suitable to identify electrical behavior of V-RFB. Parameter estimation on battery model is a process to fit an equivalent circuit into the battery. This thesis presents equivalent electrical circuit consists of actual and approximate circuit for V-RFB. The aim of this project is to propose equivalent electrical circuit for V-RFB that represents excellent adaptableness to any circuitry analysis and design. Higher number of Resistor-Capacitor (RC) branches can increase the accuracy and representation within the battery. However, it increase the complexity of the model and decrease the reduction of error speed. Actual circuit consists of an open-circuit cell potential, two ResistorCapacitor (RC) branch, a series RC, internal resistance, and inductor. From the circuit, some of the parameters are lumped to construct approximate circuit consists of opencircuit cell potential, impedance of RC branches and internal resistance with inductor. Approximate circuit is built in order to present less complex result in terms of estimation of parameter. As less parameter is estimate, it can save time computationally. Extended Kalman Filter (EKF) is used for parameter estimation for both circuit. Actual and approximate circuit are derived accordingly. From simulation result through recursive EKF algorithm of the derivation for both circuit shows each parameters smoothly approaching steady state with 0.6% and 2.0% of error, respectively. Both cell potential experiment and EKF-based estimation overlaps with minor differences for actual and approximate circuit. So, it proven that both circuit are adaptable for V-RFB.